A COMPARATIVE STUDY ON ASSESSMENT OF CRITICAL ILLNESS - Mahesh Hirulal (International Journal of Applied Ayurved Research, 2015)
Critical illness is a condition associated with many variables and unpredicted factors. In critical illness assessment of prognosis is required for prompt intervention. Ayurveda explains about prognosis by many aspects like sadhyasadhyatha of vyadhi, arista lakshana, ojokshaya etc. contemporary medical system has developed and validated many scoring system for assessment of prognosis in critically ill patients. Comparison of prognostic criteria in critically ill patients between Ayurveda methods and the modern methods of assessment. 50 critically ill patients were selected and assessed through Ayurvedic and contemporary understanding.Among critically ill patients maximum patients are from age group of 68 to 70 years i.e.40% which is belonging to vrudha vaya. In all patients bahudosha-dushya relations is noted. The 62% patients were showed ojo vyapath lakshana. Maximum of 40% patients score <7 points of GCS. Maximum of 46% patients score between 11-20 points of APACHI-II scoring system. Conclusion :In all critically ill patients bahudosha-dhushya relations are observed with the expression of predominant dosha and dhushya lakshana. The assessment of dosha, dushya, srothas, rogamarga, ojas, jnanendriya, karmendriya and arishta lakshana in critically ill patients holds good even in present scenario.